Pengembangan Aplikasi Media Pembelajaran Budidaya Burung Murai Batu Berbasis Android Menggunakan Metode Multimedia Development Life Cycle (MDLC) - Mahya’il Ahmad; Aries Saifudin (CV. Shofanah Media Berkah, 2023)
The magpie is a territorial bird and is very strong in defending its territory. Cultivating stone magpies is often a problem during the egg hatching process. Another problem in the cultivation of stone magpies is a disease such as tetelo. The learning media used by breeders as a means of learning materials in finding information about the knowledge of stone magpie cultivation is still using the internet or looking for sites in the form of websites, breeders using learning media such as websites or the internet actually tend to be less effective as a medium of learning materials. Another problem is the limited range of publication information with a special learning media system based on digital applications regarding learning stone magpie cultivation. With these problems, it makes a learning media system to help facilitate breeders in learning media using android-based applications. In developing the application the method used is the multimedia development life cycle (MDLC) method which consists of six stages, namely concept, design, material collection, creation, testing, and distribution. Because this method is very suitable with the combination of images, videos, and sounds in multimedia. The result of this research is a learning media application for stone magpie cultivation that can be used by breeders as a learning reference material about stone magpie cultivation.